The Quality of Life of Patients with Liver Cirrhosis Hospitalized at Dr. Sardjito Hospital, Yogyakarta - Sutanto Maduseno; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Liver cirrhosis is a chronic and irreversible disease. The patients quality of life (QOL) may be impaired because of long-standing burden of the disease. This research was a cross-sectional study conducted at Dr. Sardjito Hospital, Yogyakarta to determined the QOL of patients with liver cirrhosis who hospitalized in this institution. The parameter for the QOL was measured according to Spitzer index. Sixty-five patients with liver cirrhosis of various etiology were abled to be studied. The number of male and female patients were almost equal (30 and 35 respectively). There was a reduction in QOL in both male (21/30) and female (28/35) but no significant different between this variable. There was a significant positive correlation between Child criteria, and nutritional status with QOL (r=0.68, p0.05 and r=0.37, p0.05). It was concluded that Child criteria and nutritional status were positively correlated with QOL.   Key words: Liver cirrhosis, quality of life, nutritional status